Combined genetic analyses can achieve efficient diagnostic yields for subjects with Alagille syndrome and incomplete Alagille syndrome. (2nd August 2017) - Ohashi, Kei; Togawa, Takao; Sugiura, Tokio; Ito, Koichi; Endo, Takeshi; Aoyama, Kohei; Negishi, Yutaka; Kudo, Toyoichiro; Ito, Reiko; Saitoh, Shinji
Abstract: Aim: We evaluated combined genetic analyses with targeted next‐generation sequencing (NGS), multiplex ligation probe amplification (MLPA) of Jagged1 ( JAG1) genes and microarray comparative genomic hybridisation (CGH) in subjects with Alagille syndrome, incomplete clinical features of Alagille syndrome and biliary atresia. Methods: Subjects recruited from April 2013 to December 2015 underwent a targeted NGS analysis, including JAG1 and Notch homolog 2 ( NOTCH2) . If no mutations were detected in JAG1 or NOTCH2, or if copy number variations were suggested by the NGS analysis, we performed an MLPA analysis of JAG1 . We also performed a microarray CGH analysis with whole‐exon deletion detected by the MLPA analysis. Results: We analysed 30 subjects with Alagille syndrome, nine with incomplete Alagille syndrome and 17 with biliary atresia and detected pathogenic mutations in JAG1 or NOTCH2 in 24/30 subjects with Alagille syndrome and in 4/9 subjects with incomplete Alagille syndrome. No pathogenic mutations were detected in subjects with biliary atresia. The frequency of JAG1 mutations was as follows: single nucleotide variants (51.9%), small insertion or deletion (29.6%) and gross deletion (18.5%). Conclusion: Combined genetic analyses achieved efficient diagnostic yields for subjects with Alagille syndrome and incomplete Alagille syndrome.